Meaning of alcohol and other drugs and corporate practices in dependents of psychoactive substances - Silva, Priscilla Pinto Costa da; Mendes, Maria Isabel Brandão de Souza; Santos, Patricia de Jesus Costa dos; Oliveira, Bérgson Nogueira de Oliveira; Santos, Ana Raquel Mendes dos; Freitas, Clara Maria Silvestre Monteiro de (Journal of Physical Education (Maringá), 2020)
The aim of the study was to analyze the meaning of alcohol, illicit drugs and corporal practices for users of psychoactive substances that are in rehabilitation process in the CAPS ad. 76 users who’ve been rehabilitation in CAPS ad Recife / PE were interviewed. It found multiplicity in the meaning of alcohol and drugs, predominating negative factors, even considering that alcohol is initially recognized as an element of social integration. The corporal practices had positive meanings related mainly to body movement and mind occupation.